2021
DOI: 10.1002/1878-0261.12895
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking HLA genotyping and clarifying HLA impact on survival in tumor immunotherapy

Abstract: Human Leucocyte Antigen (HLA) genotyping gains intensive attention due to its critical role in cancer immunotherapy. It is still a challenging issue to generate reliable HLA genotyping results through in silico tools. In addition, the survival impact of HLA alleles in tumor prognosis and immunotherapy remains controversial. In this study, the benchmarking of HLA genotyping on TCGA is performed and a "Gun-Bullet" model which helps to clarify the survival impact of HLA allele is presented. The performance of HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The observed association of the HLA composition with the outcomes of HNSCC patients (PFS and OS) is in line with previously conducted studies, also suggesting an influence of HLA allele traits on survival [ 12 , 17 , 21 , 22 ]. For example, Wichmann et al investigated a comparable HNSCC cohort (n = 90) and reported HLA-B*13, HLA-B*35, and HLA-B*51 as independent predictors of PFS in HNSCCs [ 12 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…The observed association of the HLA composition with the outcomes of HNSCC patients (PFS and OS) is in line with previously conducted studies, also suggesting an influence of HLA allele traits on survival [ 12 , 17 , 21 , 22 ]. For example, Wichmann et al investigated a comparable HNSCC cohort (n = 90) and reported HLA-B*13, HLA-B*35, and HLA-B*51 as independent predictors of PFS in HNSCCs [ 12 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…For MHC-II genotyping there is currently no consensus about the best method. Several benchmarks have been performed previously [14,[16][17][18][19][20][21][22][23], but these were either not applied to MHC class II or did not include some recently published tools.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution six-digit HLA typing was then inferred with HLA-HD v 1.3, 69,70 based on the nomenclature of the IPD-IMGT-HLA database v. 3.40. 71 This tool previously showed its ability to provide an highly accurate HLA inference (miscall rate <4%) in independent studies 72,73 and was crossvalidated in our cohort, for patients with available SSO-PCR HLA typing (Table S14).…”
Section: Dna Isolationmentioning
confidence: 82%